Proteomic analysis reveals that CD147/EMMPRIN confers chemoresistance in cancer stem cell‐like cells. Issue 10 (23rd April 2013) - Kang, Min Jueng; Kim, Hwang‐Phill; Lee, Kyeong‐seob; Yoo, Young‐Dong; Kwon, Yong‐Tae; Kim, Kristine M.; Kim, Tae‐You; Yi, Eugene C.
Abstract : Cancer stem cells (CSCs) are a subpopulation of tumor cells that can self‐renew, metastasize, and promote cancer recurrence. A comprehensive characterization of the CSC proteome has been hampered due to their scarcity and rapid differentiation. Here, we present a systematic analysis of the cell‐surface proteome using a CSC‐like cell line derived from MDA‐MB453 breast cancer cells, which exhibited a CD44 + /CD24 − (where CD is cluster of differentiation) phenotype and chemoresistance. We identified differentially expressed proteins in CSC‐like cells, including upregulated plasma membrane proteins such as CD44, CD133, epidermal growth factor receptor (EGFR), CD147, cadherin 1, integrins, and catenin (cadherin‐associated protein), beta 1 (CTNNB1), using an in‐situ biotinylation approach followed by MS analysis. We examined the role of CD147 in the promotion of CSC growth and survival, and demonstrated that inhibition of CD147 with a monoclonal antibody induced significant inhibition of cell growth. siRNA‐mediated silencing of CD147 gene expression restored the sensitivity of CSC‐like cells to 5‐fluorouracil (5‐FU), along with decreasing the expression of thymidylate synthase, p‐AKT, and β‐catenin, while increasing the expression of p‐glycogen synthase kinase (GSK)3β. Increased CD147 expression in the CSC‐like cells, as seen by proteomic analysis, and the functional consequences of CD147 overexpression in CSC‐like cells suggest that CD147 may be one of the critical cell‐surface proteins involved in promoting chemoresistance and survival in CSCs.